TIME MANAGEMENT PRACTICES OF EDUCATORS IN A STATE UNIVERSITY - Lualhati, Genalyn P (PUPIL: International Journal of Teaching, Education and Learning, 2019)
This descriptive study revealed the time management practices of the faculty members in a state university in the Philippines. By employing self-made questionnaire, data on time management practices along with scheduling, goal setting, prioritizing tasks, managing paperwork and managing interruptions and challenges met by the teachers on managing their time were gathered. Analyses of the treated data showed that the respondents practiced scheduling, goal setting, prioritizing task, managing paperwork, and managing interruptions and excessive paperwork and reports is a common challenge met by the faculty members in managing their time. This study offered recommendations that may contribute significantly to their success as an educator and person.